2019
DOI: 10.1534/g3.119.400353
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Chilling Tolerance in Sorghum Dissected with a Nested Association Mapping Population

Abstract: Dissecting the genetic architecture of stress tolerance in crops is critical to understand and improve adaptation. In temperate climates, early planting of chilling-tolerant varieties could provide longer growing seasons and drought escape, but chilling tolerance (<15°) is generally lacking in tropical-origin crops. Here we developed a nested association mapping (NAM) population to dissect the genetic architecture of early-season chilling tolerance in the tropical-origin cereal sorghum (Sorghum bicolor [L.] Mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 84 publications
(139 reference statements)
7
87
0
Order By: Relevance
“…In breeding and genetics studies, chilling tolerance is most often characterized through seedling emergence rate and seedling vigor scores, usually based on visual evaluation (Burow et al, 2011; Franks et al, 2006; Marla et al, 2019; Parra-Londono et al, 2018). By contrast, crop models simulate days to emergence, seedling biomass weight, and leaf area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In breeding and genetics studies, chilling tolerance is most often characterized through seedling emergence rate and seedling vigor scores, usually based on visual evaluation (Burow et al, 2011; Franks et al, 2006; Marla et al, 2019; Parra-Londono et al, 2018). By contrast, crop models simulate days to emergence, seedling biomass weight, and leaf area.…”
Section: Discussionmentioning
confidence: 99%
“…For planting dates in early and mid June, CERES-Sorghum has shown satisfactory predictions for anthesis, grain yield, and evapotranspiration across Kansas (Araya et al, 2017; Staggenborg and Vanderlip, 2005; White et al, 2015). To evaluate the model accuracy in predicting days to emergence for a chilling-tolerant genotype (Kaoliang), simulations were conducted to match field experiments that were planted in April, May, and June in 2016–2018 at three sites in Kansas (Marla et al, 2019). For these simulations, cultivar specific-parameters (G) were obtained for full-season hybrids (80 days to anthesis and 140 days to physiological maturity) and short-season hybrids (60 days to anthesis and 110 to physiological maturity) (Araya et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of cold tolerance identified eight regions associated with final emergence percentage (FEP) and seedling survival (SR) on chromosomes SBI-01, -02, -03, -06, -09 and -10 (Parra-londono et al 2018b ). Colocalisation of chilling tolerance loci with grain tannin and dwarfing genes further indicated that selection for nontannin and dwarfing alleles in early grain sorghum breeding inadvertently resulted in chilling sensitivity (Marla et al 2019 ). Similarly, heat stress affects sorghum growth and photosynthesis.…”
Section: Genomic Research In Sorghummentioning
confidence: 99%
“…While sorghum germplasm resources are diverse and under development for early season chilling tolerance (Chopra et al 2015, Marla et al 2019, Moghimi et al 2019, Ostmeyer et al 2020), the potential for early season microbial-enhanced chilling tolerance in sorghum has not yet been explored. Simultaneously evaluating diverse sorghum genotypes for genetic chilling tolerance and microbe-enhanced chilling tolerance would leverage a novel synergistic approach to early season chilling tolerance.…”
Section: Introductionmentioning
confidence: 99%